2007
DOI: 10.1111/j.1478-5153.2007.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and physicians’ viewpoints regarding children visiting/not visiting adult ICUs

Abstract: Allowing children to visit adult intensive care units (ICUs) has been an area of controversy. There is a lack of recent research dealing with visits by children and physicians' views and whether differences exist between the views held by nurses and physicians regarding visits by children. The aim of this study was to describe and compare reasons given by nurses and physicians for restricting visits by children to a relative hospitalized in an adult ICU. This was a quantitative, descriptive multicentre study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
26

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 28 publications
1
20
0
26
Order By: Relevance
“…Few institutions have policies for children visits to adult ICU; (5,6,10,11) in some, this analysis depends on individual circumstances and common sense. (11) Two recent studies conducted in Italy found similar results. The first identified that from 104 ICUs, only 22% allowed children below 12 years-old visits.…”
Section: Review On Children Visiting Intensive Care Unitmentioning
confidence: 99%
See 4 more Smart Citations
“…Few institutions have policies for children visits to adult ICU; (5,6,10,11) in some, this analysis depends on individual circumstances and common sense. (11) Two recent studies conducted in Italy found similar results. The first identified that from 104 ICUs, only 22% allowed children below 12 years-old visits.…”
Section: Review On Children Visiting Intensive Care Unitmentioning
confidence: 99%
“…(5) The restrictions to children visits to adult ICUs are often based on the fear of exposing the child to hospital infection, (2)(3)(4)(5)(6)(7) However there is no literature evidence of this. In a multicenter quantitative trial (11) aimed to understand the reasons provided by the teams for restricting children visits to adult ICUs, 36% answered that their main reason was fear of infection. However, some of these respondents mentioned that both physicians and nurses use this explanation to disguise a certain emotional unpreparedness to deal with children who have severely ill relatives in the unity.…”
Section: Review On Children Visiting Intensive Care Unitmentioning
confidence: 99%
See 3 more Smart Citations